Perceptions of classroom learners and distant learners, in the BBA program, regarding total experiential learning / Kamel Taufiq Abdul Ghani and Che Faridah Che Mahmood - Abdul Ghani, Kamel Taufiq; Che Mahmood, Che Faridah (2003)
The fundamental objective of this descriptive research is to highlight full-time and part-time Bachelor of Business Administration (BBA) students' attitudes towards and perceptions of total experiential learning. As learning requires a collaborative effort between student and teacher, this survey hopes to serve as a tool to better comprehend the behaviour of UiTM's customers — its students. Understanding the characteristics and perceptions of learners would thus enable UiTM to fine tune the programs towards fulfilling the customers' needs and delivering an effective academic program, especially the BBA program.